2013
DOI: 10.1039/c3nr02190d
|View full text |Cite
|
Sign up to set email alerts
|

Continuously manufactured magnetic polymersomes – a versatile tool (not only) for targeted cancer therapy

Abstract: Micromixer technology was used to prepare polymeric vesicles (Pluronic® L-121) dual loaded with the anti-cancer drug camptothecin and magnetic nanoparticles. Successful incorporation of the magnetic nanoparticles was confirmed by transmission electron microscopy. Dynamic light scattering measurements showed a relatively narrow size distribution of the hybrid polymersomes. Camptothecin polymersomes reduced the cell viability of prostate cancer cells (PC-3) measured after 72 h significantly, while drug-free poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…Similarly to liposomes and niosomes, polymersomes enable multiple loading of a water‐soluble cargo in the inner volume as well as hydrophobic components in the membrane layer . The micromixer technology was employed to prepare polymersomes in a continuous way using commercial tri‐block copolymer poly(ethylene oxide) 5 ‐ b ‐poly(propylene oxide) 68 ‐ b ‐poly(ethylene oxide) 5 (Pluronic L‐121) dually loaded with the anticancer drug camptothecin and magnetic nanoparticles . Magnetic polymersomes are of high interest as theranostic nanocarriers for monitoring drug delivery.…”
Section: Polymer‐based Colloidal Carriersmentioning
confidence: 99%
“…Similarly to liposomes and niosomes, polymersomes enable multiple loading of a water‐soluble cargo in the inner volume as well as hydrophobic components in the membrane layer . The micromixer technology was employed to prepare polymersomes in a continuous way using commercial tri‐block copolymer poly(ethylene oxide) 5 ‐ b ‐poly(propylene oxide) 68 ‐ b ‐poly(ethylene oxide) 5 (Pluronic L‐121) dually loaded with the anticancer drug camptothecin and magnetic nanoparticles . Magnetic polymersomes are of high interest as theranostic nanocarriers for monitoring drug delivery.…”
Section: Polymer‐based Colloidal Carriersmentioning
confidence: 99%
“…It was shown that SPION could be incorporated into polymersomes formed by the self-assembly of various amphiphilic block copolymers. [21][22][23] The vascular endothelium is regarded today as a major endocrine/paracrine/autocrine organ that plays a fundamental role in the regulation of the cardiovascular system. 20 Moreover, the possibility of further functionalization, e.g., by the covalent attachment of targeting peptides and/or fluorescent labels can be considered to broaden possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanocapsules containing iron oxide nanoparticles and anticancer drugs have been designed to provide highly magnetic carriers under moderate gradient magnetic fields for tumor penetration, which are responsive to remote RF field for ON-OFF switchable drug release [52]. The encapsulation of hydrophobically coated IONPs from ferrofluids together with camptothecin anticancer drug into PPO block of Pluronic vesicles, provided a scalable continuous manufacturing procedure to obtain multi-core theranostic drug delivery vehicles [99], which is a promising step in consolidating recent achievements in targeted drug delivery to cancer cells.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%